THE EFFECT OF ONLINE LECTURES AND PPL II ON STUDENT READINESS TO BECOME TEACHERS - Hasanah, Mahmudah; Sa’bandi, Agus Reza; Nor, Baseran (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Field Lectures and Teaching Practice (PPL) is a training ground for FKIP students to determine the various knowledge, attitudes, and skills of teachers so that they can carry out their duties and responsibilities professionally, as well as the framework for forming professional teachers. However, what is happening in the field is that the implementation of PPL online has not been maximized because there are many inhibiting factors such as quotas, networks, inadequate devices from students and the students themselves, and also online learning media platforms which are still underutilized by teachers or students, resulting in difficulties. Carry out learning interactions. The purpose of this research is to explain the effect of implementing lectures and PPL II online on the readiness of students to become teachers. The researcher wants to explain the causal relationship between lectures and PPL II, which affects student readiness to become teachers data processing using SEM Analysis. The analytical tool used is LISREL. The study results show that lectures and PPL II influence student readiness to become teachers. Furthermore, students agree or are ready for readiness to become teachers after the implementation of PPL II, even though it is online.